IMPLEMENTASI SISTEM HIDROPONIK PEMBENIHAN CABE MERAH DENGAN BERBASIS GREEN HOUSE DI KABUPATEN PANDEGLANG - Alimuddin, Alimuddin (Jurnal Balireso: Jurnal Pengabdian pada Masyarakat, 2019)
Red chili (Capcicum Annum L) is one of the horticulture plants that has high economic value, canprovide employment and improve the standard of living of farmers. Red chili is one of the leadingcommodities of the national and Banten provinces, where the planting is almost spread throughoutthe territory of Indonesia. Red chili is a commodity that is needed by all levels of society. Red chiliis rich in carbohydrates, protein, fat, flavonoids, capsaicin, minerals, water, fiber and rich invitamin C and provitamin A. The need for red chili always increases along with population growthand diverse needs. Pandeglang is known as one of the largest vegetable cultivation areas in BantenProvince. The need for seeds for one hectare planting area requires around 2-3 Kg of chili (300?500 gr of chili seeds) with high economic value. The aim is to implement a hydroponic and greenhouse system for Red Chili hatchery cultivation in Pandeglang district. Methods used Theapplication of technology carries out technological engineering in the development of red chillicultivation in the hydroponic and green house planting media to improve the quality of red chilliseeds in Pandeglang district. Tahapan is the dissemination of community service implementationto industry partners with program objectives in Mandalawangi sub-district, hydroponic kitassembly, and building green houses. Results, the implementation of hydroponic making activitiesfor the cultivation of red chilli seeds and the making of green houses, FGDs or training andmentoring of red chilli seedlings, FGD Making Hydroponic Kits, FGDs making Green House.